What social media data mean for audience studies: a multidimensional investigation of Twitter use during a current affairs TV programme - D'heer, Evelien; Verdegem, Pieter (Information, communication & society, 2015)
Both practitioners and researchers embrace the increasing volume of digital data to measure and understand audiences. This study focuses on Twitter use during an eminent Belgian current affairs television (TV) programme to investigate how people talk about TV on Twitter. The main objective of the study is to understand how we can interpret these digital traces and, in extension, discuss its utility and value for audience studies. More specifically, we define two validity issues related to the use of social media data: that is, the technological bias of data analysis and the alleged objectivity of the data. These issues are addressed through the combination of Twitter data and user insights. In particular, we focus on interaction patterns and the content of Twitter messages in relation to TV content. We compliment these analyses with in-depth interviews with a selection of Twitter users. The results confirm the variations and complexities of the use of digital objects such as the @-sign and the hashtag. In addition, although Twitter messages are unobtrusive measures, they reflect performances in the sense that they entail interpretations as well as representations of the self and one's programme taste. Users predominantly feel the need to scrutinize the actions and utterances of politicians and experts. The use of irony and sarcasm exemplifies the playfulness and fun factor of these activities. To conclude, we elaborate on the results in relation to the validity issues we put forth and discuss methodological and epistemological concerns related to the use of social media data in audience studies.